The Role of Artificial Intelligence in Improving the Efficiency of Financial and Accounting Performance: A Field Study on some Sudanese business organizations - Hammad, Suleiman Musa Elzain (Journal of Economic, Administrative and Legal Sciences, 2025)
The main objective of the study is to know the role that artificial intelligence, with its various technologies, can play in improving financial and accounting performance. To achieve the study’s objectives, the researcher adopted inductive approach, historical approach and the descriptive analytical approach in analyzing field study data, and obtaining results, in addition, (150) questionnaire forms distributed to some employees in some Sudanese business organizations in Port Sudan and Atbara, only (140) questionnaire forms collected, which represent (93.3%). The study’s findings revealed that, using artificial intelligence to prepare accurate and transparent financial reports facilitates understanding financial status of Sudanese business organizations and developing financial strategies. Moreover, using artificial intelligence the digital transformation of accounting transactions save the time and reduces accounting errors in Sudanese business organizations. The study recommended that, Sudanese business organizations should adopt artificial intelligence technologies into their financial and accounting operations in order to improve the efficiency of their financial and accounting performance. In addition to conducting more studies to determine the impact of artificial intelligence on the auditing, financial analysis profession and rationalizing decisions.